Comparative analysis of the epidemiological characteristics of adenovirus, rotavirus A, and coinfection in children during 2014–2023 in Guangzhou, China - Yuqian Yan; Zhiwei Zeng; Huixin Gao; Shanshui Zeng; Siqin Duan; Jun Jiang; Xiaolan Ai; Lanlan Zeng; Shuwen Yao; Yan Long (Virology Journal)
Abstract Background Infection is the cause of diarrhoea, and rotaviruses and adenoviruses are important pathogens in children. Methods A retrospective study was conducted on 144,067 children with diarrhoea between 2014 and 2023 in China. We used the colloidal gold method to detect intestinal adenovirus and rotavirus A antigens in faeces. The epidemiological characteristics of these viruses and the impact of meteorological factors on them were analysed before and after coronavirus disease 2019 (COVID-19) pandemic. Results During this decade, the positive rate of adenovirus infection was 6.41%, while the positive rate of rotavirus A infection was 11.81%, higher than that of adenovirus infection. The positive rate of adenovirus and rotavirus A coinfection was 1.92%. The positive rates of adenovirus, rotavirus A and coinfection showed a fluctuating trend, and suddenly decreased in 2020. There was an apparent decrease of positive rate of rotavirus A, with a decrease of 57.27%, during 2020–2023. Surprisingly, the positive rate of adenovirus infection exceeded that of rotavirus A infection in 2021 and 2023. During the COVID-19 pandemic, the proportion of female patients and children over two years of age infected with adenovirus or rotavirus A increased, while the proportion of cases in winter decreased. In addition, we found that the positive rate of rotavirus A infection was related to average temperature and sunshine, and the positive rate of adenovirus and rotavirus A coinfection was only related to sunshine. However, these correlations disappeared during the COVID-19 pandemic. Conclusions This study revealed the recent prevalence of adenovirus and rotavirus A infections in children with diarrhoea in south-central China and provided a theoretical basis for the prevention and control of viral diarrhoea.